(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A few decades ago, teaching profession was considered as an ecstatic, euphoric, fascinating, lucrative, rapturous occupation owing to lesser working hours, restful and peaceful working environment, plenty of holidays, minimum hurdles, handsome emoluments and respect and prestige. If an individual had to make a choice between teaching profession and other vocations, such as office and administrative job, then teaching job was given preference over other options. In other words teaching employment was most preferred by employment aspirant.Gone are those days when teaching occupation was considered an amiable, calming and restful employment in India. In last three decades, teaching job has gone under tremendous changes. Since, change is the law of nature and same also applies to the teaching profession. Recommendations of various education commissions and different education policies have put more accountability, responsibilities, expectations, challenges and pressure on teaching community. Further the commercialisation of education has the toughened circumstances and states of affairs.